TAHLIL AKHTO’ AL-IMLAIYYAH WANNAHWIYAH FII AL-INSYA’ AL-‘ARABI WATAKHTU AN-NAMTHI AL-MUNASABI FII TA’LIMIHI BIMA’AAHAD AL-KAUTSAR ALGONTORY AIKMEL LOMBOK ASY-SYARQIYAH (The Center for Language Development, Mataram State Islamic University., 2022)
This study aims to analyze forms of imla' and nahwu errors in the third and fourth grader students' insha' writing at Al Kautsar Al Gontory Islamic Boarding School as a basis for designing an appropriate insha' learning model. This study is qualitative descriptive.The study indicates that the third-grader students commit 11 types of imla' errors and 14 types of nahwu errors. On the other hand, the fourth-grader learners make 12 and 7 errors of imla' and nahwu, respectively. Other errors are the absence of opening and closing of insha' and punctuation marks.The learning model applied in insha' learning at school is the PBJL with a student-centered learning approach and uses the assignment method. However, the results suggest that the learning design suitable for the school based on several considerations is direct learning with a teacher-centered learning approach and using an expository strategy. Lecturing and question-answer are the appropriate methods to apply such strategy. Suppose the teacher wants to devote 1 hour of lessons involving students to correct their insha’ writing errors. In that case, a discovery learning strategy with a student-centered is appropriate for this applied to the discussion method. Keywords: Imla' and Nahwu's Errors, Learning Model, Insha' Learning.